STRATEGI PENDIDIKAN ISLAM DALAM MENGHADAPI TANTANGAN TEKNOLOGI DIGITAL PADA PESERTA DIDIK MELALUI PENDIDIKAN KARAKTER - Rosmasita Siregar; Rosmalia Hrp; Padillah Amanda Nasution (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
The rapid development of digital technology has had a significant impact on the field of education, particularly on the character formation of students who live in an era of unlimited information. Although digitalization offers various opportunities—such as easy access to knowledge, interactive learning media, and expanded learning spaces—it also presents serious challenges, including digital inequality, exposure to negative content, cyberbullying, and reduced direct social interaction. This study employs a library research method by reviewing relevant literature, scientific journals, and written works to analyze strategies in Islamic education for shaping student character in the digital era. The findings indicate that Islamic education plays a crucial role in cultivating moral, spiritual, and social values through character education, which includes religiosity, nationalism, independence, cooperation, and integrity. Digital-era challenges such as imbalance in social media use, digital safety risks, cyberbullying, and plagiarism require educators to implement creative teaching approaches, digital supervision, role modeling, and strong digital literacy. The study concludes that character education based on Islamic values is an essential strategy for developing students who are not only intellectually capable but also morally upright, critical, and responsible in navigating rapid technological advancements. Collaboration among teachers, families, and communities is vital to ensure consistent and effective character development.